Dance Training Improves Cytokine Secretion and Viability of Neutrophils in Diabetic Patients - Borges, Leandro; Passos, Maria E. P.; Silva, Maysa B. B.; Santos, Vinicius C.; Momesso, César M.; Pithon-Curi, Tania C.; Gorjão, Renata; Gray, Stuart R.; Lima, Kauê C. A.; de Freitas, Paulo B.; Hatanaka, Elaine (Mediators of Inflammation, 2019)
Background. Evidence suggests that exercise improves neutrophil function. The decreased functional longevity of neutrophils and their increased clearance from infectious sites contribute to the increased susceptibility to infection and severity of infection observed in patients with diabetes. Objective. Herein, we investigated the effects of a dance program on neutrophil number, function, and death in type 2 diabetes mellitus (T2DM) patients and healthy volunteers. Methods. Ten patients with T2DM and twelve healthy individuals participated in a moderate-intensity dance training program for 4 months. The plasma levels of leptin, free fatty acids (FFAs), tumour necrosis factor-α (TNF-α), C-reactive protein (CRP), interleukin-1β (IL-1β), and interleukin-1 receptor antagonist (IL-1ra); neutrophil counts; extent of DNA fragmentation; cell membrane integrity; and production of TNF-α, interleukin-8 (IL-8), interleukin-6 (IL-6), and IL-1β in neutrophils were measured before and after training. Results. Training reduced plasma levels of TNF-α (1.9-fold in controls and 2.2-fold in patients with T2DM) and CRP (1.4-fold in controls and 3.4-fold in patients with T2DM). IL-1ra levels were higher in the control group (2.2-fold) after training. After training, neutrophil DNA fragmentation was decreased in patients with T2DM (90%), while the number of neutrophils increased (70% in controls and 1.1-fold in patients with T2DM). Conclusion. Dance training is a nonpharmacological strategy to reduce inflammation and improve neutrophil clearance in patients with T2DM.